A systematic review: the influence of real time feedback on wheelchair propulsion biomechanics. (2nd January 2018) - Symonds, Andrew; Barbareschi, Giulia; Taylor, Stephen; Holloway, Catherine
Abstract: Background: Clinical guidelines recommend that, in order to minimize upper limb injury risk, wheelchair users adopt a semi-circular pattern with a slow cadence and a large push arc. Objectives: To examine whether real time feedback can be used to influence manual wheelchair propulsion biomechanics. Review methods: Clinical trials and case series comparing the use of real time feedback against no feedback were included. A general review was performed and methodological quality assessed by two independent practitioners using the Downs and Black checklist. The review was completed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines. Results: Six papers met the inclusion criteria. Selected studies involved 123 participants and analysed the effect of visual and, in one case, haptic feedback. Across the studies it was shown that participants were able to achieve significant changes in propulsion biomechanics, when provided with real time feedback. However, the effect of targeting a single propulsion variable might lead to unwanted alterations in other parameters. Methodological assessment identified weaknesses in external validity. Conclusions: Visual feedback could be used to consistently increase push arc and decrease push rate, and may be the best focus for feedback training. Further investigation is required to assess such intervention during outdoor propulsion. Implications for Rehabilitation: Upper limb pain and injuries are common secondary disorders that negatively affect wheelchair users' physical activity and quality of life. Clinical guidelines suggest that manual wheelchair users should aim to propel with a semi-circular pattern with low a push rate and large push arc in the range in order to minimise upper limbs' loading. Real time visual and haptic feedback are effective tools for improving propulsion biomechanics in both complete novices and experienced manual wheelchair users.